The Oxford handbook of U.S. national security - Gvosdev, Nikolas K. 1969-; Reveron, Derek S.; Cloud, John 1953- (Oxford handbooks, 2018)
"The Oxford Handbook of US National Security frames the context, institutions, and processes the US government uses to advance national interests through foreign policy, government institutions, and grand strategy. Contributors examine contemporary national security challenges and the processes and tools used to improve national security."...Provided by publisher